2010
DOI: 10.1089/fpd.2009.0409
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliIsolates from Broiler Chicken Meat, Broiler Chickens, Pork, and Pigs Share Phylogroups and Antimicrobial Resistance with Community-Dwelling Humans and Patients with Urinary Tract Infection

Abstract: Escherichia coli is the most common cause of urinary tract infection (UTI). Phylogroup B2 and D isolates are associated with UTI. It has been proposed that E. coli causing UTI could have an animal origin. The objective of this study was to investigate the phylogroups and antimicrobial resistance, and their possible associations in E. coli isolates from patients with UTI, community-dwelling humans, broiler chicken meat, broiler chickens, pork, and pigs in Denmark. A total of 964 geographically and temporally ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 39 publications
10
84
0
Order By: Relevance
“…Similar to other studies worldwide, the majority of the FEC isolates were phylogenetic group C, A and B1 (Hiki et al, 2014;Jakobsen et al, 2010;Sola-Gines et al, 2015). In this current study, fifty percent of the CEC isolates belonged to phylogenetic group A, which is typically identified as a commensal, non-pathogenic E. coli (Clermont et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to other studies worldwide, the majority of the FEC isolates were phylogenetic group C, A and B1 (Hiki et al, 2014;Jakobsen et al, 2010;Sola-Gines et al, 2015). In this current study, fifty percent of the CEC isolates belonged to phylogenetic group A, which is typically identified as a commensal, non-pathogenic E. coli (Clermont et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…by Jakobsen et al (2010), found E. coli isolates sourced from human patients, broiler meat and other food-producing animals, including pigs, could not be differentiated on the basis of their VGs nor their AMR profile. They found resistant isolates clustered in the same phylogenetic group regardless of the source of the isolates (Jakobsen et al, 2010).…”
Section: Public Health Significance Of Apecmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, ESBLproducing Enterobacteriaceae isolates have shifted from the hospital to the community and the environment [41]. ESBL-producing Enterobacteriaceae have been recovered from different sources in the community, including cattle, chickens, pigs, raw milk and lettuce [42][43][44]. Recent study from India reported that a substantial number of tap water samples were contaminated with carbapenemase blaNDM-1 producing organisms [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, E. coli carrying extended-spectrum beta-lactamases (ESBL) and AmpC ß-lactamases (AmpC) are increasingly being considered as an emerging public health concern. Antimicrobial resistant E. coli (Gousia et al, 2011;Jakobsen et al, 2010) and VRE (Freitas et al, 2011;Gambarotto et al, 2001;Kempf et al, 2008;Manero et al, 2006) have been isolated from pigs and pork. ESBL-and AmpCproducing bacterial strains and genes relevant for public health have also been reported in pigs and pork products (in particular CTX-M, TEM-52, SHV-12 and CMY-2) (EFSA, 2011b).…”
Section: Hazards Considered But Not Included In the Assessmentmentioning
confidence: 99%